Morfología de rugas palatinas en pacientes adultos de la Clínica Odontológica (2021)
Oral cavity is an excellent data source for forensic science. The palatal ruga, irregular soft tissue of the front third of the hard palate, is a recognized adjunct pattern in forensic and medico legal investigation for the identification of a person. It have population morphological patterns characteristics of palatal rugas.